Innovations in ion-selective optodes: a comprehensive exploration of modern designs and nanomaterial integration - Barhoum, Ahmed; Alhashemi, Yaser; Ahmed, Yomna M.; Rizk, Mahmoud S.; Bechelany, Mikhael; Abdel-Haleem, Fatehy M. (Frontiers in Bioengineering and Biotechnology, 2024)
In recent years, ion-selective optodes (ISOs) have remarkably progressed, driven by innovative modern designs and nanomaterial integration. This review explored the development of modern ISO by describing state-of-the-art strategies to improve their sensitivity, selectivity, and real-time monitoring capacity. The review reported the traditional membrane based-optodes, and investigated the latest research, current design principles, and the use of essential components, such as ionophores, indicator dyes, polymer membranes, and nanomaterials, in ISO fabrication.Special attention was given to nanomaterials (e.g. quantum dots, polymer dots, nanospheres, nanorods and nanocapsules) and particularly on how rare earth elements can further enhance their potential. It also described innovative ISO designs, including wearable optodes, smartphone-based optodes, and disposable paper-based optodes. As the pursuit of highly sensitive, selective, and adaptable ion sensing devices continues, this summary of the current knowledge sets the stage for upcoming innovations and applications in different domains (pharmaceutical formulations, medical diagnosis, environmental monitoring, and industrial applications).